Non-Invasive Assessment of the Liver – Serum Markers and Imaging Techniques - Mania, Anna; Kemnitz, Paweł; Mazur-Melewska, Katarzyna; Figlerowicz, Magdalena; Służewski, Wojciech (IntechOpen, 2011)
None